A dual-signal output ratiometric electrochemiluminescent sensor for NADH detection. Issue 17 (30th July 2019) - Chen, Hongjun; Liu, Xiu; Yin, Cheng; Li, Wang; Qin, Xiangdong; Chen, Changya
Abstract : NADH can amplify the anodic ECL response of NGQDs, while it can diminish the cathodic ECL response of NGQDs. Based on the proposed principle, a dual-signal output ratiometric method is proposed to detect NADH without additional coreactant. Abstract : Ratiometric electrochemiluminescence (ECL) has attracted great attention in the field of electrochemical analysis. In this study, a dual-signal-output ratiometric ECL sensor was developed for the detection of nicotinamide adenine dinucleotide (NADH). Nitrogen-doped graphene quantum dots (NGQDs) exhibit double ECL signal output capability, without the requirement of additional coreactants. NADH can amplify the anodic ECL response of NGQDs, while it can diminish the cathodic ECL response of NGQDs. Based on the principle between relative enhancing ECL intensity ratio and NADH concentrations, the constructed ratiometric ECL sensor was applied to NADH assays, with a wide concentration range of 10–400 μM and a low limit of detection (LOD) of 2.5 μM (S/N = 3). Furthermore, the proposed method was applied for the determination of spiked NADH, which was proved to be feasible in the biological sample matrix. The proposed strategy of modulating multiple-ECL signals of the single NGQD emitter not only provides a new ECL system for the accurate detection of NADH but also broadens the design pathway for ratiometric sensing fabrication.